Thermoelectric Measurement of a Single, TiO2-Catalyzed Bi2Te3 Nanowire - S. Hoda Moosavi; Danny Kojda; Maximilian Kockert; Piet Schoenherr; Thorsten Hesjedal; Saskia F. Fischer; Michael Kroener; Peter Woias (Proceedings, 2017)
We report on the functionality of our Thermoelectric Nanowire Characterization Platform (TNCP). As a proof of concept of our design, we present a set of experimental results obtained from the characterization of a single Bi2Te3 nanowire, allowing for the determination of the nanowire’s electrical conductivity and Seebeck coefficient.